2021
DOI: 10.24996/ijs.2021.62.9.29
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Healthcare System for Chronic Ailments using Machine Learning Techniques – a Review

Abstract: World statistics declare that aging has direct correlations with more and more health problems with comorbid conditions. As healthcare communities evolve with a massive amount of data at a faster pace, it is essential to predict, assist, and prevent diseases at the right time, especially for elders. Similarly, many researchers have discussed that elders suffer extensively due to chronic health conditions.  This work was performed to review literature studies on prediction systems for various chronic illnesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Another systematic literature review by Battineni et al suggested that in real-time clinical practice, there is no universally accepted approach for determining the optimal method, as each machine learning technique comes with its own set of strengths and limitations, however, Support Vector Machines (SVM) and Logistic Regression (LR) are two common machine learning methods that are used in most of the studies [ 94 ]. In another review article, the majority of the examined studies emphasized that the use of only machine learning methods or combining it with other intelligent techniques is popularly used to prevent emergencies [ 95 ]. This approach holds a significant promise for uncovering substantial patterns in both structured and unstructured datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic literature review by Battineni et al suggested that in real-time clinical practice, there is no universally accepted approach for determining the optimal method, as each machine learning technique comes with its own set of strengths and limitations, however, Support Vector Machines (SVM) and Logistic Regression (LR) are two common machine learning methods that are used in most of the studies [ 94 ]. In another review article, the majority of the examined studies emphasized that the use of only machine learning methods or combining it with other intelligent techniques is popularly used to prevent emergencies [ 95 ]. This approach holds a significant promise for uncovering substantial patterns in both structured and unstructured datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabic letters Meem and Seen obtained the highest classification accuracy, reaching 100%, for the ten Arabic fonts in the sizes 8-72, while for the small font sizes (14)(15)(16)(17)(18)(19)(20), the classification accuracy rate reached 90 percent. The accuracy for the letters Aeen, Taa, Haa, Laam, and Waaw is perfect and has reached 100% to classify in sizes from 14 to 72 for all fonts.…”
Section: Cmfmentioning
confidence: 95%
“…The review mainly focused on shallow machine learning algorithms such as support vector machine, decision tree, Bayesian network, artificial neural network, etc. [8] conducted a review on elderly healthcare system based on shallow machine learning algorithms. The paper review the machine learning technique for detecting chronic ailment in elderly person.…”
Section: Introductionmentioning
confidence: 99%